Developing Canva-Based Video Tutorials to Enhance Poetry Writing Skills in Vocational High School Students - Salihin Salihin; Nursaid Nursaid (AL-ISHLAH: Jurnal Pendidikan, 2025)
This study aimed to develop and assess the effectiveness of a Canva-based video tutorial as instructional media to enhance poetry writing skills among tenth-grade vocational high school (SMK) students in Batam. The research addresses the gap between students' preference for digital learning tools and the continued reliance on conventional, text-based teaching methods in language instruction. Using a Research and Development (RD) approach, the study adopted the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). A needs analysis involving students and teachers identified a low interest in textbook-based learning and a dominant preference for visual and digital media. Based on these findings, a structured and visually engaging video tutorial was developed through Canva, incorporating step-by-step guidance for writing poetry. The media underwent expert validation by specialists in media, language, and pedagogy, receiving high ratings for validity (average 91%). Practicality tests with students and teachers indicated high ease of use, appeal, and instructional value (94% practicality score). Effectiveness was measured through a pretest-posttest design with 39 students, analyzed using an independent t-test. Results showed a significant improvement in students’ poetry writing scores (t = 6.642, p 0.05). The findings demonstrate that the Canva-based video tutorial is a valid, practical, and effective tool for teaching poetry writing. This study underscores the pedagogical value of integrating digital tools in language learning, particularly in enhancing literacy, creativity, and student engagement in vocational education contexts.